Microfinance games - Gine, Xavier; World Bank. (Washington, D.C. : World Bank, 2006)
"Microfinance has been heralded as an effective way to address imperfections in credit markets. But from a theoretical perspective, the success of microfinance contracts has puzzling elements. In particular, the group-based mechanisms often employed are vulnerable to free-riding and collusion, although they can also reduce moral hazard and improve selection. The authors created an experimental economics laboratory in a large urban market in Lima, Peru and over seven months conducted 11 different games that allow them to unpack microfinance mechanisms in a systematic way. They find that risk-taking broadly conforms to predicted patterns, but that behavior is safer than optimal. The results help to explain why pioneering microfinance institutions have been moving away from group-based contracts. "--World Bank web site.
Title from PDF file as viewed on 8/23/2006.
Includes bibliographical references.
Also available in print.
System requirements: Adobe Acrobat Reader.
Mode of access: World Wide Web.
Zahid
Keywords: Microfinance -- Peru -- Lima; Game theory